Gestão socioambiental em micro e pequenas indústrias de Pau dos Ferros-RN - Paiva, Francisco Cleiton da (Universidade Federal Rural do Semi-Árido, 2016)
This study aimed to analyze the manager‟s perception of micro and small industries companies regarding to social and environmental practices in the city of Pau dos Ferros-RN. It sought to verify whether these companies make use of social and environmental management, while identifying its practices and pointing out the motivations, barriers and opportunities for its implementation. Beside it, the study also aimed to describe the negative and positive consequences perceived by some managers from the existing social and environmental practices, and therefore identify their knowledge on the subject. The study presents a theoretical approach to Sustainability and Sustainable Development, Environmental and Social Responsibility Management based on authors like Boff (2012), Elkington (2012), Barbieri (2011), Dias (2011), Donaire (2013), Aligleri et. al. (2009), Nascimento, Lemos and Mello (2008), Tachizawa and Andrade (2012) and Sachs (2009), among others, with a view to questioning the aspects relating to environmental management practices in object of research companies. It was also discussed theoretical aspects about the Micro and Small Enterprises, specific aspects related to industrial activity and environmental management related to this business segment, from authors such as Resnik (1990), Ferronato (2011), Farias and Teixeira (2002) , Andrade (2002), as well as works published by institutions like Sebrae, FIRJAN and IPEA, which supported that part of the job. From this perspective, this study is classified as to its nature as qualitative research; about the objectives of the research, defined as descriptive; and, as to the object, a field survey is considered. As data collection instrument interviews were conducted with managers of micro and small industries companies Pau dos Ferros-RN, addressing the Environmental Management at their companies from their perceptions, and then an interpretative analysis, based on data obtained. Research has shown all respondents have the notion of the importance of the environment and that most of them develop some environmental practices, mainly focused on the energy and water savings, some performing reuse of materials. Social-oriented stocks are scarce and are not directly related to the environmental strategy of the company. Largely not considered difficult to invest or develop environmental initiatives, although I realize that this requires incentives from governments, which does not occur with any of the companies interviewed. Managers, mostly understand that environmental actions result in positive impacts for companies, such as cost reduction, image enhancement on the market, increasing competitiveness and their sales, hardly noticing the negative aspects of these practices. In addition, respondents felt that their companies even being micro or small, have an importance for the community, mainly due to the generation of employment and income is vital to the development of the city and region
Environmental management in micro and small industries in the city of Pau dos Ferros – RN
Keywords: Gestão Socioambiental; Sustentabilidade; Micro e Pequenas Indústrias; Environmental Management; Sustainability; Micro and Small Industries; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE